Beyond the Algorithm: How Medical Professionals Validate AI Outputs for Clinical Use - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into clinical practice—from diagnosing diabetic retinopathy to detecting pulmonary nodules—heralds a new era of...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Precision Medicine